2021
DOI: 10.3390/antiox10050633
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of H2S on Obesity-Associated Metabolic Disturbances

Abstract: Over the last several decades, hydrogen sulfide (H2S) has gained attention as a new signaling molecule, with extensive physiological and pathophysiological roles in human disorders affecting vascular biology, immune functions, cellular survival, metabolism, longevity, development, and stress resistance. Apart from its known functions in oxidative stress and inflammation, new evidence has emerged revealing that H2S carries out physiological functions by targeting proteins, enzymes, and transcription factors thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 195 publications
(238 reference statements)
0
9
0
4
Order By: Relevance
“…H 2 S increases glucose absorption in skeletal muscle, improves insulin sensitivity and modulates circadian clock genes in myocytes. The hypothalamic CBS (cystathionin-β-synthase)/H 2 S pathway reduces obesity [ 54 ] and improves insulin sensitivity through brain–adipose interactions. Most studies have shown that plasmatic H 2 S levels are lower in diabetic patients [ 50 , 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…H 2 S increases glucose absorption in skeletal muscle, improves insulin sensitivity and modulates circadian clock genes in myocytes. The hypothalamic CBS (cystathionin-β-synthase)/H 2 S pathway reduces obesity [ 54 ] and improves insulin sensitivity through brain–adipose interactions. Most studies have shown that plasmatic H 2 S levels are lower in diabetic patients [ 50 , 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…The latter can react with H 2 S forming protein persulfides. However, in the obesity a decreased synthesis of H 2 S means an oxidizing environment in which protein sulfenic acids are oxidized to sulfonic acid leading to protein inactivation [ 162 ]. This hypothesis seems to be confirmed by a recent study that determined protein persulfidation in various tissues of mice under dietary restriction (DR) [ 163 ].…”
Section: Reactive Sulfur Species In Diseasesmentioning
confidence: 99%
“…У регуляції функціонального стану нирок важливу роль відіграє гідроген сульфід (Н 2 S), який впливає на ниркову гемодинаміку, проявляє протизапальні, протифібротичні та протиапоптичні властивості [13]. При ожирінні порушується ендогенна продукція Н 2 S, але роль цих метаболічних змін є дискутабельною [4]. Зокрема, отримані суперечливі дані щодо впливу донорів Н 2 S на масу тіла лабораторних тварин за умов високожирової дієти [7,21].…”
Section: вступunclassified